2018
DOI: 10.1002/ceat.201800048
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Longitudinal Vortex Generator Configuration on the Hydrodynamics in a Novel Spouted Bed

Abstract: The gas-solid flow in a cylindrical spouted bed with a pair of spherical longitudinal vortex generators (LVGs) was numerically investigated by a two-fluid model with kinetic theory for granular flow. Simulations and analyses were conducted on five types of spouted beds: a conventional spouted bed without disturbance units as well as spouted beds with a pair of LVGs in which the radius of spheres installed on the LVGs had four different dimensions. Results of the computational fluid dynamics demonstrate that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…Spout deflection is a typical instability phenomenon in spouted and spout-fluidized beds. It can cut-off the normal particle movement circulation, which is the resort of high interaction efficiency of the gas–solid phases in spouted and spout-fluidized beds. Thus, to eliminate the spout deflection and achieve stable spouting quality, various modifications to the reactor geometry have been tried, such as adjusting the gas inlet device shape, adjusting the slot angle, ,, and installing draft plates. However, these modifications have side effects on the hydrodynamics of gas–solid systems, such as lowering the solid circulation velocity or enhancing the spout incoherence . Moreover, the fundamentals related to spout deflection have not been well understood, especially under various operational conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Spout deflection is a typical instability phenomenon in spouted and spout-fluidized beds. It can cut-off the normal particle movement circulation, which is the resort of high interaction efficiency of the gas–solid phases in spouted and spout-fluidized beds. Thus, to eliminate the spout deflection and achieve stable spouting quality, various modifications to the reactor geometry have been tried, such as adjusting the gas inlet device shape, adjusting the slot angle, ,, and installing draft plates. However, these modifications have side effects on the hydrodynamics of gas–solid systems, such as lowering the solid circulation velocity or enhancing the spout incoherence . Moreover, the fundamentals related to spout deflection have not been well understood, especially under various operational conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al 14 studied the gas−particle flow behavior in a 3D conical spouted bed using the TFM. Wu et al 15 investigated the gas−solid flow in a cylindrical spouted bed with a pair of spherical longitudinal vortex generators by the TFM. Their results showed that the turbulent kinetic energy of the gas phase in the spouted bed was promoted significantly by the longitudinal vortex.…”
Section: Introductionmentioning
confidence: 99%
“…When the jet diameter D = 4 mm, the number of jets is 24, and the nondimensional cross-sectional area of the air inlet is 0.67, the fluidization effect between fluids in the bed is optimal. In the case of spouted beds with LVGs, the law of fluid flow is explored by changing the number of rows, spacing, and diameter of the spherical generators. The simulation showed that when the number of rows of the spherical generators was 3, the spacing was 10 mm, and the diameter was 28 mm, the turbulence effect of the particles was the strongest.…”
Section: Introductionmentioning
confidence: 99%